Acute effect of whole-body vibration combined with stretching on bridge performance in artistic gymnasts - George, D.; Vasilis, K.; Giorgos, P. (Journal of Biology of Exercise, 2012)
The purpose of this study was to examine the acute effect of Whole-Body Vibration combined with stretching (WBVS) on flexibility of shoulder's joint in relation to bridge performance. Twelve artistic gymnasts that where dropped out from their competition duties (23,00 ± 2,29 years, 56,91 ± 6,23 kg, 164,08 ± 4,83 cm) composed the WBVS, and 12 female students of Department of Physical Education composed the control group (non vibration-stretching group: NVS) (20,33 ± 0,78, 58,91 ± 5,18 kg, 165,50 ±4,01 cm). Both groups performed an 1-minute intervention program on a Whole Body Vibration platform that was turn on for WBVS, whereas NVG performed the same intervention program with the device was turn off. The total sample was assessed on bridge performance. Vibration (30Hz, 2mm displacement) was applied to two sites, four times for 10 seconds, with 10 sec of rest between times and one minute rest between sites. According to the results both groups improved "bridge performance" after the end of intervention program and remain this improvement for at least 60 minutes. Whoever, WBVS had ignificant increase flexibility than NVS. Conclusively, Whole-Body Vibration combined with stretching on shoulders joint may greatly influence flexibility in bridge performance.